Revisiting the Nexus between Turkish Tourism Index Returns and Economic Policy Uncertainty: Partial Wavelet Coherence Analysis - Ceylan, Özcan (Journal of Applied And Theoretical Social Sciences, 2023)
This study reevaluates the well-documented negative relationship between the Turkish tourism index stock returns and economic policy uncertainty (EPU) indices using a wide range of EPU indices that span from 1997 to 2003. The aim of the paper is to find out whether EPU indices a have particular importance for the tourism companies’ stock returns or they end up with the same consequences regardless of the sector. To this end, Partial Wavelet Coherence analysis is conducted using the BIST 100 and the real effective exchange rate indices as conditioning variables. Results show that the negative relationship between the EPU indices and Turkish tourism index returns tends to disappear when controlled for the BIST 100 index returns. EPUs are shown to have no particular effect on the excess stock return performance of Turkish tourism companies. The policy uncertainties in Europe (particularly in France and, to a lesser extent in Germany) become effective only after controlling also for the changes in real effective exchange rates.